Surgical Outcomes in Patients with Simultaneous Traumatic Brain and Torso Injuries in a Single Regional Trauma Center over a 5-Year Period - Jung-Ho Yun (Journal of Trauma and Injury)
Purpose The purpose of the study is to analyze the results of surgical treatment of patients with brain and torso injury for 5 years in a single regional trauma center. Methods We analyzed multiple trauma patients who underwent brain surgery and torso surgery for chest or abdominal injury simultaneously or sequentially among all 14,175 trauma patients who visited Dankook University Hospital Regional Trauma Center from January 2015 to December 2019. Results A total of 25 patients underwent brain surgery and chest or abdominal surgery, with an average age of 55.4 years, 17 men and eight women. As a result of surgical treatment, there were 14 patients who underwent the surgery on the same day (resuscitative surgery), of which five patients underwent surgery simultaneously, four patients underwent brain surgery first, and one patient underwent chest surgery first, four patients underwent abdominal surgery first. Among the 25 treated patients, the 10 patients died, which the cause of death was five severe brain injuries and four hemorrhagic shocks. Conclusions In multiple damaged patients require both torso surgery and head surgery, poor prognosis was associated with low initial Glasgow Coma Scale and high Injury Severity Score. On the other hand, patients had good prognosis when blood pressure was maintained and operation for traumatic brain injury was performed first. At the same time, patients who had operation on head and torso simultaneously had extremely low survival rates. This may be associated with secondary brain injury due to low perfusion pressure or continuous hypotension and the traumatic coagulopathy caused by massive bleeding.